KARAKTERISTIK PASIEN NYERI PUNGGUNG BAWAH DI POLIKLINIK REHABILITASI MEDIK RUMAH SAKIT DAERAH KOTA TIDORE KEPULAUAN PERIODE JANUARI-JUNI 2019 - Zhari Zafitri Goin; Lely M Pontoh; Hilmi Umasangadji (Fakultas Kedokteran, Universitas Khairun, 2020)
Background: Low back pain (LBP) is a musculoskeletal disorder characterized by discomfort in the lower back (lumbosacral) region which can be acute or chronic and has a variety of causative factors. NPB is included in the top 10 diseases with the highest prevalence in the world. There are several risk factors for low back pain, such as individual, occupational and environmental factors. Methode: This research is qualitative-descriptive study, held on 1st desember 2019 until 31st Desember 2019 at the Polyclinic of Medical Rehabilitation in Regional Hospital Tidore Kepulauan, which aims to determine the characteristics of patients with LBP in Medical Rehabilitation Polyclinic of Regional Hospital Tidore Kepulauan in January 2019 until June 2019. Number of LBP patients that came to Medical Rehabilitation polyclinic in January-June 2019 was 41 people and there were 34 samples collected by using total sampling technique. The result of this research was secondary data obtained from patient medical record and presented in frequency distribution table form with explanation result. Result and conclusion: The results showed that LBP patients who came to Medical Rehabilitation Polyclinic in Regional Hospital Tidore Kepulauan in January 2019 until June 2019 is mostly in the age group of 61-70 years is 14 samples (41,2%), female (50%) and male (50%), PNS is 18 samples (52,9%) and most diagnosed with hernia nuclei pulposi is 19 samples (55,9%). Keywords: hernia nuclei pulposi , low back pain, medical rehabilitation